2020
DOI: 10.1108/cc-06-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic resources by law academics: a case study from the University of Namibia

Abstract: Purpose The purpose of this paper is to examine the use of e-resources by the Faculty of Law’s academic staff at the University of Namibia’s (UNAM’s) main campus. The study aimed to determine their level of awareness of electronic resources (e-resources) available to them, how useful and effective they found these e-resources, and the challenges they face in accessing them. Design/methodology/approach A convenient sampling technique was used to select a sample of 12 law academics from the population of 17. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Researchers, teaching staff, and students use EIRs for various purposes, such as academic purposes (i.e., course works, completing assignments, research, compiling teaching and learning materials, preparing seminar presentations, and disseminating and preserving research findings), acquiring development ideas, communicate and collaborate with friends and classmates, improve knowledge, online registration, materials for a writing project, career development, efficient retrieval of information, curriculum design, and recreation. 5,15,[19][20][21][22][23][24][25][26] Electronic information resources in academic libraries are essential to researchers, teaching staff, and students because they provide a comprehensive and vast amount of information that users can quickly and cheaply access in electronic forms in its latest form: 5,10,27 it helps users to advance their research work; 28 it is readily available as long the users have access to the network or internet connectivity; 4 flexible in terms of storage and interoperable since they are dynamic resulting into the wide dissemination of information; convenience since a piece of data can be easily searched, 5,6 EIRs can easily and simultaneously be accessed by multiple off-campus users in a short period; 8 EIRs are up-to-date, trustworthy, and appropriate, access a wide variety of information, and the time and location of access are unlimited and unrestricted and saves physical spaces. 6,29 Mollel and Mwantimwa (2019) 13 observed that library EIR usage depends on the relevancy of the content and users' skills to navigate the different electronic resource platforms, search engines, and interfaces.…”
Section: Use Of Eirs In Academic Librariesmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers, teaching staff, and students use EIRs for various purposes, such as academic purposes (i.e., course works, completing assignments, research, compiling teaching and learning materials, preparing seminar presentations, and disseminating and preserving research findings), acquiring development ideas, communicate and collaborate with friends and classmates, improve knowledge, online registration, materials for a writing project, career development, efficient retrieval of information, curriculum design, and recreation. 5,15,[19][20][21][22][23][24][25][26] Electronic information resources in academic libraries are essential to researchers, teaching staff, and students because they provide a comprehensive and vast amount of information that users can quickly and cheaply access in electronic forms in its latest form: 5,10,27 it helps users to advance their research work; 28 it is readily available as long the users have access to the network or internet connectivity; 4 flexible in terms of storage and interoperable since they are dynamic resulting into the wide dissemination of information; convenience since a piece of data can be easily searched, 5,6 EIRs can easily and simultaneously be accessed by multiple off-campus users in a short period; 8 EIRs are up-to-date, trustworthy, and appropriate, access a wide variety of information, and the time and location of access are unlimited and unrestricted and saves physical spaces. 6,29 Mollel and Mwantimwa (2019) 13 observed that library EIR usage depends on the relevancy of the content and users' skills to navigate the different electronic resource platforms, search engines, and interfaces.…”
Section: Use Of Eirs In Academic Librariesmentioning
confidence: 99%
“…The low usage of EIRs in Africa became a concern for many librarians; hence, studies were done, and the results varied from one study to another. For example, the survey conducted by Leonard et al (2020) 15 on electronic resources by law academics at the University of Namibia found that 100% of the Law faculty members were aware of the e-resources subscribed to, although the usage of the resources remained low. The studies by Yebowaah (2017), 32 Ahmed and Al-Reyaee (2017), 33 and Adeleke and Nwalo (2017) 34 reported that the majority of the users were aware of electronic resources and also highlighted the benefits of the awareness of EIRs to the academic community.…”
Section: Electronic Information Resources Awareness In Academic Libra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among such studies of the re-structuring library services model, knowing about library users' awareness and uses preferences of resources format is especially important to this study. Ngema and Masenya (2020), Leonard et al (2020), Alfiras and Bojiah (2020) and Odumade-Salako and Amusan (2019) conducted studies to know the level of awareness and usage preference of resources format. All studies found that most respondents preferred to use e-resources and had a high level of awareness.…”
Section: Literature Reviewmentioning
confidence: 99%